Design And Validation Of A Digital Competency Questionnaire For Research - Sánchez, Adrián; Lagunes, Agustín; Torres, Carlos; Judikis Preller, Juan Carlos; López, Francisco (My University, 2019)
Currently, citizens find themselves in a technological environment that demands a series of digital skills that must be developed to perform adequately, either in society or in any type of profession. It is of our interest that these competences allow students to perform satisfactorily in the academic field. Thus, the need to establish the level of digital skills that students require in order to carry out scientific research in a satisfactory manner. For this reason, an instrument of self-perception was adapted that gives a diagnosis of digital competences for research conducted by new university students. In order to carry out the analysis of reliability and validity of the instrument, a pilot test was implemented with a representative sample of 71 new students, belonging to a military engineering university in Veracruz, Mexico. As a result of the analysis, the instrument obtained a remarkable reliability, yielding a Cronbach's Alpha of 0.890 and its construct validity was average, obtaining a global Kaiser Meyer Olkin index of 0.718. Regarding the level of competence detected, a better perception of development was obtained in the students coming from private schools and technological baccalaureates, while the lowest levels were found in those coming from CONALEP, COBAEV and tele-baccalaureates. In light of the results, it is important to visualize the factors that can affect the academic development of students in order to allow them to enter universities with a better expectation of success.
Keywords: Digital competences for research; new income; self-perception